A taxonomic revision of the world Smodicini (Coleoptera, Cerambycidae) - Martins, Ubirajara R. (Arquivos de Zoologia, 1975)
The six genera at present included in the Cerambicyd tribe Smodicini, are monographed. The tribe is mainly Neotropical, but two genera occur in Africa, one of which, Afrosmodicum, is described as new (type-species, Smodicum ebeninum Chevrolat, 1855). Both African genera are monotypic. Metaphrenon is described, to include the single Antillean species Smodicum impressicolle Lacordaire, 1869. Smodicum Haldeman, 1847, the largest genus of the tribe, which in the past received most species described, including the African ones, is now redefined to include 13 species, distributed from the United States to Argentina. The following species of Smodicum are described as new: clancularium (from Mexico, Quintana Roo), longicorne (from Brazil, Minas Gerais to Santa Catarina), recticolle (from Argentina, Santiago del Estero), and torticolle (from Colombia). The following new synonymies ore established in Smodicum: subcylindricum Thomson, 1878 = brunneum Thomson, 1878; argentinum Bruch, 1911 = cucujiforme (Say, 1826); missionum Bruch, 1911 = di-nellii Bruch, 1911; peninsulare Linsley, 1942 and arizonarium Knull, 1966 = pacificum Linsley, 1934; and bonariense Bruch, 1911 = semipubescens Gounelle, 1911.